Analysis of Whole Exome Sequence Data from African Patients with HD-Like Features and No Known HDPhenocopy Syndrome - Naicker, Racilya; Naicker, Racilya (University of the Witwatersrand, Johannesburg, 2023)
Huntington disease (HD) is a rare progressive neurodegenerative disorder that results from a CAG repeat expansion within the huntingtin gene (HTT). Several syndromes present with HD- like features in the absence of the HTT expansion and are termed HD phenocopies. Huntington disease-like 2 (HDL2), a known phenocopy, is most commonly observed in individuals with African, or probable African, ancestry. Therefore, previous diagnostic testing in the Division of Human Genetics, National Health Laboratory Service (Johannesburg, South Africa) screened for both HD and HDL2 in patients with HD-like phenotypes and an indication of African ancestry. Patients who tested negative for both syndromes remain undiagnosed, highlighting the need for further testing strategies. This study aimed to identify variants implicated in the HD-like phenotype of these patients. In a group of nine undiagnosed patients with Black African ancestry, a virtual gene panel was analysed through a whole exome sequencing (WES) approach. The data was filtered, and candidate variants were prioritised according to the frequency, type, and location of the variants as well as in-silico pathogenicity prediction scores. A total of 20 candidate variants in 15 genes were shortlisted and classified according to ACMG/AMP guidelines. Notably, variants in the mitochondrial DNA polymerase subunit gamma (POLG; c.2246T>C; p.Phe749Ser) and the glutaryl-CoA dehydrogenase (GCDH; c.877G>A; p.Ala293Thr) genes were classified as likely pathogenic and pathogenic, respectively. Genotype-phenotype correlation indicated a potential diagnosis of autosomal dominant progressive external ophthalmoplegia in the patient carrying the POLG variant, whereas the GCDH variant was considered an incidental finding due to a lack of correlation with the characteristics of glutaric aciduria type 1. These findings highlight the diagnostic challenges faced in the African context for patients with HD-like clinical features and call for further validation studies and re-analysis of the WES data using alternative gene panels for the patients for whom no putative pathogenic variants were identified
A research report (in the format of a “submissible” paper) submitted in partial fulfillment of the requirements for the degree of Master of Science in Medicine (Genomic Medicine) by Research and Coursework to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023
Keywords: Huntington Disease; Huntington Disease Phenocopies; Whole Exome Sequencing; Virtual GenePanel; South Africa; UCTD; SDG-3: Good health and well-being